Sterols compositions, antibacterial, and antifouling properties from two Malaysian seaweeds: Dictyota dichotoma and Sargassum granuliferum - Kamariah Bakar, Habsah Mohamad, Hock Seng Tan, Jalifah Latip (Journal of Applied Pharmaceutical Science, 2019)
Seaweeds or macroalgae are the primary producers of an oceanic food source, widely distributed across the globe and known for their excellent defensive properties against numerous biotic and abiotic factors. These defensive traits come from their secondary metabolites that act as protective barriers against pathogens and harmful organisms where among these compounds some have been found possessing the antifouling characteristic. In this study, Dictyota dichotoma and Sargassum granuliferum collected from Pulau Nunuyan Laut, Sabah, Malaysia, were studied to determine its sterol composition, and isolation was carried out to isolate their pure sterol compounds. Two assays consist of disk diffusion method for antibacterial activity and crystal violet assay were carried out to study its antifouling activity. Campesterol, stigmasterol, and β-sitosterol were the dominant sterol compound detected in both samples and six pure sterols were isolated (compounds 1–6). Results from the antibacterial and antifouling analysis showed better inhibition for Gramnegative compared to Gram-positive bacteria. Fucosterol (4) and epicoprostanol (5) gave the best antibacterial activity with two bacteria inhibited compared to other compound. Meanwhile, coprostanol (1), campesterol (2), stigmasterol (3), epicoprostanol (5), and 5β-cholestan-3-one (6) showed strong antifouling activity towards the selected bacterial strains with IC50 values ranges from 266.3 to 425.8 µg/ml.
Keywords: Dictyota dichotoma, Sargassum granuliferum, antibacterial, antifouling, sterol, seaweeds.